2013
DOI: 10.1007/s11548-013-0966-8
|View full text |Cite
|
Sign up to set email alerts
|

A laboratory comparison of computer navigation and individualized guides for distal radius osteotomy

Abstract: Compared to navigated DRO, individualized guides were easier to use, faster, and produced more precise correction of ulnar variance and radial inclination. The combination of true three-dimensional planning, ease of use, and accurate and precise corrective guidance makes the individualized guide technique a promising approach for performing corrective osteotomy of the distal radius.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(31 citation statements)
references
References 30 publications
1
30
0
Order By: Relevance
“…14 A randomised laboratory trial comparing traditional preparation with 3D model preparation for distal radius osteotomy found that model use resulted in shorter operations with more precise correction of ulnar variance and radial inclination. 15 …”
Section: Introductionmentioning
confidence: 99%
“…14 A randomised laboratory trial comparing traditional preparation with 3D model preparation for distal radius osteotomy found that model use resulted in shorter operations with more precise correction of ulnar variance and radial inclination. 15 …”
Section: Introductionmentioning
confidence: 99%
“…One year after surgery, the patient had symmetric strength and range of motion of her wrist and was pain free. The measured errors are slightly higher compared to in-vitro experiments [27,51], where an average Fig. 18 Postoperative accuracy evaluation of the combined intra-and extra-articular osteotomy presented in Sect.…”
Section: Resultsmentioning
confidence: 90%
“…Although they offer superior accuracy [25], navigation systems have been losing popularity since they are costly and laborious to use. Originating from dental surgery [26] and thanks to recent advances in additive manufacturing, the production of patient-specific instruments has instead become a cost-effective and promising alternative to navigation systems [27]. Although the use of patient-specific guides for corrective osteotomies of long bones was described [11,18,[28][29][30][31][32][33][34], the main application of patient-specific guides in orthopedic surgery is currently arthroplasty [35].…”
Section: Introductionmentioning
confidence: 99%
“…After osteotomy, the pin pairs are inserted into a reduction guide to achieve reduction [10]. Other techniques use drilling and cutting guides to predrill holes for subsequent fixation using standard osteosynthesis material [11], or by using patient-specific fixation plates that provide accurate alignment of the bone segments [4, 12, 13]. All these approaches may reduce the surgical error but do not allow any deviation from the preoperative plan in cases where the planned rotation angle appears unfeasible during surgery.…”
Section: Discussionmentioning
confidence: 99%